2016
DOI: 10.1093/hmg/ddw248
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental alterations and seizures developed by mouse model of infantile hypophosphatasia are associated with purinergic signalling deregulation

Abstract: Hypomorphic mutations in the gene encoding the tissue-nonspecific alkaline phosphatase (TNAP) enzyme, ALPL in human or Akp2 in mice, cause hypophosphatasia (HPP), an inherited metabolic bone disease also characterized by spontaneous seizures. Initially, these seizures were attributed to the impairment of GABAergic neurotransmission caused by altered vitamin B6 (vit-B6) metabolism. However, clinical cases in human newborns and adults whose convulsions are refractory to pro-GABAergic drugs but controlled by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
2
45
0
1
Order By: Relevance
“…In a mouse model of hypophosphatasia, low levels of the inhibitory neurotransmitter, GABA, were demonstrated in 1995 . However, seizures in patients with hypophosphatasia are refractory to pro‐GABAergic drugs and other experiments on the hypophosphatasia mouse show downregulation of P2X7 receptors and reduction of seizures by blockade of P2X7 receptors, suggesting the anticonvulsive effects of vitamin B 6 may be due to its capacity to block P2X7R receptors …”
Section: Causes and Consequences Of Plp Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of hypophosphatasia, low levels of the inhibitory neurotransmitter, GABA, were demonstrated in 1995 . However, seizures in patients with hypophosphatasia are refractory to pro‐GABAergic drugs and other experiments on the hypophosphatasia mouse show downregulation of P2X7 receptors and reduction of seizures by blockade of P2X7 receptors, suggesting the anticonvulsive effects of vitamin B 6 may be due to its capacity to block P2X7R receptors …”
Section: Causes and Consequences Of Plp Deficiencymentioning
confidence: 99%
“…46 However, seizures in patients with hypophosphatasia are refractory to pro-GABAergic drugs and other experiments on the hypophosphatasia mouse show downregulation of P2X7 receptors and reduction of seizures by blockade of P2X7 receptors, suggesting the anticonvulsive effects of vitamin B 6 may be due to its capacity to block P2X7R receptors. 47,48 Recent metabolomic profiling of the brains of mice with hypophosphatasia showed a complex range of abnormalities including low levels of GABA and another important neurotransmitter, adenosine, as well as abnormalities of metabolites involved in myelin synthesis (N-acetylaspartate [NAA], N-acetylglutamate [NAG]), and in the methionine cycle and transsulfuration pathway (cystathionine and methionine). 49 Studies on vitamin B 6 -deprived Neuro-2a cells showed reduced synthesis of glycine, serine, and 5-methyl-tetrahydrofolate.…”
Section: Epilepsymentioning
confidence: 99%
“…A role for post-transcriptional control of the P2X7R expression has been proposed and therapeutic targeting of microRNA-22 was suggested to prevent development of epilepsy and inflammation ( Jimenez-Mateos et al, 2015 ). Purinergic signalling, via P2X7R, regulates neonatal seizures associated with hypophosphatasia, an inherited metabolic bone disease characterised by spontaneous seizures ( Sebastián-Serrano et al, 2016 ). P2X7R antagonists were effective against hypoxia-induced neonatal seizures in mice ( Rodriguez-Alvarez et al, 2017 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…Although the exact consequences of these mutations on brain development have not been clarified yet, TNAP knock-out mice show abnormalities in myelination and synaptogenesis (Hanics et al, 2012 ), and subjects with hypophosphatasia suffer from seizures (Whyte, 2010 ), thus indicating defects in neurotransmission and/or in neurodevelopment (Fonta et al, 2015 ). Recent data have now started to link these defects and clinical manifestations to altered purinergic transmission, with the first demonstration of a direct involvement of an aberrant P2X7 activation in the alterations of hippocampal and cortex structure and in the development of seizures in TNAP −/− mice, due to high ATP concentrations as a consequence of reduced TNAP activity (Sebastián-Serrano et al, 2016 ). This observation would greatly help the development of possible new pharmacological approaches to the pathology.…”
Section: Neurodevelopmental Disorders Associated To Alterations In Pumentioning
confidence: 99%